Prevalensi brucellosis pada ternak di jawa tengah: evaluasi metode rose bengal test dan complement fixation test di balai besar veteriner wates, yogyakarta (2024–2025) - Ahmad Alifudin; Faruq Iskandar; Roisu Eny Mudawaroch (Fakultas Pertanian Universitas Majalengka, 2025)
Brucellosis is a strategic zoonotic disease that significantly affects animal health, human health, and the livestock economy. This study aimed to evaluate the effectiveness of the Rose Bengal Test (RBT) as a screening method and the Complement Fixation Test (CFT) as a confirmatory diagnostic tool using serum samples collected from various districts and cities in Central Java. The research was conducted at the Regional Veterinary Laboratory (Balai Besar Veteriner) in Wates, Yogyakarta, from April to June 2025. A total of 3,393 serum samples were examined. The RBT results showed a higher number of reactive cases compared to the CFT outcomes; however, several reactive samples were not confirmed as positive upon retesting with the CFT. Boyolali recorded the highest number of confirmed cases (12 cases), followed by Kudus (6 cases), Batang (2 cases), and Banyumas (1 case). The findings demonstrate that RBT serves as a rapid and practical screening tool, yet confirmation through CFT remains essential to ensure diagnostic accuracy. These results emphasize the need for combining laboratory diagnostic methods with strict biosecurity implementation and livestock monitoring, particularly in densely populated farming areas.